Subacromial Injection Results in Further Scapular Dyskinesis. Issue 8 (6th August 2014) - Ettinger, Luke; Shapiro, Matthew; Karduna, Andrew
Background: Scapular kinematic movement patterns between patients with subacromial impingement and healthy controls have been extensively investigated. However, a high degree of variability has been reported in the literature pertaining to differences between these 2 groups. Purpose: To investigate the influence of subacromial pain on scapular kinematics. Study Design: Controlled laboratory study. Methods: A total of 21 patients with stage 2 subacromial impingement who received local anesthetic injections as part of their normal treatment were recruited for this study. The postinjection kinematic data from these patients were compared with those of healthy age-, sex-, and arm dominance–matched controls. Results: Subacromial injections of anesthetics resulted in increased scapular anterior tilting; however, no changes were noted in upward or internal rotation. When compared with healthy controls, patients had greater anterior tilting and upward rotation of the scapula. Conclusion: The study findings indicate that the removal of pain in patients with impingement results in further dyskinesis of the scapula. Clinical Relevance: Pain may be causing patients with subacromial impingement to limit scapular tilt and upward rotation, and movement limitations may continue after an anesthetic injection.